Characteristics of Nori-Like Product Prepared from Seaweeds Growing in Indonesia. Issue 6 (3rd July 2022) - Sinurat, Ellya; Fransiska, Dina; Utomo, Bagus Sediadi Bandol; Subaryono,; Nurhayati,; Sihono,
ABSTRACT: Nori is a dried edible seaweed product used in Japanese cuisine made originally from seaweed from the genus Porphyra. Porphyra usually grows in sub-tropic coastal waters and is rarely found in tropical zones like Indonesia. For this reason, it is important to find local raw materials to substitute Porphyra to produce nori-like products in Indonesia. The present work aimed to study the physicochemical characteristics, fatty acid profiles, color components, and mineral contents of nori-like products formulated from seaweeds growing in Indonesia. The seaweeds used were Gracilaria verrucosa, Ulva lactuca, and  Caulerpa racemosa . The proportion of each seaweed for nori-like product formulation was 100:0:0; 75:25:0; 75:0:25; 50:50:0; 50:0:50, and 50:25:25, respectively. Based on color, dietary fiber, and minerals (Mg and Ca), the formula of nori-like product processed from Gracilaria and Ulva with the proportion of 50:50 had a better than the commercial nori.